Practical aspects of infective endocarditis prevention - G. G. Taradin; G. A. Ignatenko; I. V. Rakitskaya; E. Yu. Ponomareva; N. T. Vatutin; Yu. D. Bondarenko (Кардиоваскулярная терапия и профилактика)
The review is devoted to the practical aspects of infective endocarditis (IE) prevention, the issues of which, as before, remain the subject of lengthy discussions. Despite repeatedly updated national and international guidelines on this topic, medical practitioners are not always fully aware of antibiotic prophylaxis of IE. After a brief consideration of the etiological, pathogenetic features and risk factors of the disease, the main provisions of 2015 European Society of Cardiology guidelines on IE prevention, which were approved by the Russian Society of Cardiology, are presented. The categories of patients with the highest risk of IE, procedures associated with an increased risk of IE (dental and other invasive procedures) are described in detail. The main practical approaches to the identification of risk groups and performing invasive procedures that influence the decision to prescribe antibiotic prophylaxis are described. Particular attention is paid to the characteristics of both first-line antibiotic drugs and alternative agents for penicillin allergy or in cases of β-lactamase secreting pathogens.